2019
DOI: 10.4172/2161-1122.1000533
|View full text |Cite
|
Sign up to set email alerts
|

Health from the Hive: 5% Propolis Mouth Wash as an Adjunct in the Treatment of Chronic Generalized Gingivitis-A Randomized Controlled Clinical Trial

Abstract: Background: Gingival diseases affect 80% of the adult population in India and are considered to be plaque initiated inflammatory conditions with the presence of pathogenic bacteria. The term, Gingivitis means inflammation of the gums or gingiva. Gingivitis is a non-destructive type of periodontal disease if left untreated gingivitis can progress to periodontitis. Thus it can eventually lead to loss of teeth. It is a well-known fact that all periodontitis are initiated by gingivitis. Objectives: To assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Another result of our study, in comparing the mean changes of the GI after using mouthwashes, propolis reduced the GI similar to CHX, and no significant difference was found, consistent with the results of the study by Savita et al 17 Contrary to our results, studies by Dodwad and Kukreja, 19 Arjun et al, 18 Krishna et al, 20 and Porwal et al 22 showed that propolis reduced GI significantly better than CHX, which might be explained by the effect of regional flora on honeybee nutrition and the production of propolis with different compositions and effects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Another result of our study, in comparing the mean changes of the GI after using mouthwashes, propolis reduced the GI similar to CHX, and no significant difference was found, consistent with the results of the study by Savita et al 17 Contrary to our results, studies by Dodwad and Kukreja, 19 Arjun et al, 18 Krishna et al, 20 and Porwal et al 22 showed that propolis reduced GI significantly better than CHX, which might be explained by the effect of regional flora on honeybee nutrition and the production of propolis with different compositions and effects.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, in comparison of PI and GI of the whole oral cavity before and after using 0.2% CHX mouthwash and propolis mouthwash, both mouthwashes significantly reduced the mean PI and G, consistent with studies by Savita et al, 17 Arjun et al, 18 Dodwad and Kukreja, 19 and Krishna et al 20 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mouth rinse has been quite popular due to its ease of use; however, chemical compounds found in mouth rinses such as cetylpyridinium chloride, chlorhexidine and zinc chloride may have side effects if used for long term [257,258]. Propolis-based mouth rinse or mouthwashes have been studied by several researchers and observed great potential in reducing dental plaque and gingival inflammation [259][260][261][262][263]. A patent (CN104739738A) was granted for a mouthwash made with propolis to improve oral health and to treat oral diseases [264].…”
Section: Bee Product-based Mouthwashmentioning
confidence: 99%
“…a) Research by Kripal et al [63] assessed the effectiveness of propolis 5% mouthwash in chronic generalized gingivitis and compared the effectiveness of 5% propolis mouthwash to chlorhexidine mouthwash. This study was conducted on a sample of 45 patients randomly selected in the 18-70 years age group, divided into 3 groups: Group I with 15 patients treated with 5% propolis mouthwash, group II with 15 patients treated with the control group chlorhexidine gargle, and group III with 15 patients treated with normal saline (placebo).…”
Section: Propolis Biocompatibility In Clinical Studiesmentioning
confidence: 99%